Experimental and Computational Studies on a Base‐Free Terminal Uranium Phosphinidene Metallocene. Issue 70 (11th November 2020) - Wang, Deqiang; Ding, Wanjian; Hou, Guohua; Zi, Guofu; Walter, Marc D.
Abstract: The first stable base‐free terminal uranium phosphinidene metallocene is presented; and its structure and reactivity have been studied in detail and compared to that of the corresponding thorium derivative. Salt metathesis reaction of the methyl iodide uranium metallocene Cp'''2 U(I)Me (2, Cp'''= η 5 ‐1, 2, 4‐(Me3 C)3 C5 H2 ) with Mes*PHK (Mes*=2, 4, 6‐(Me3 C)3 C6 H2 ) in THF yields the base‐free terminal uranium phosphinidene metallocene, Cp'''2 U=PMes* (3 ). In addition, density functional theory (DFT) studies suggest substantial 5f orbital contributions to the bonding within the uranium phosphinidene [U]=PAr moiety, which results in a more covalent bonding between the [Cp'''2 U] 2+ and [Mes*P] 2− fragments than that for the related thorium derivative. This difference in bonding besides steric reasons causes different reactivity patterns for both molecules. Therefore, the uranium derivative 3 may act as a Cp'''2 U(II) synthon releasing the phosphinidene moiety (Mes*P:) when treated with alkynes or a variety of hetero‐unsaturated molecules such as imines, thiazoles, ketazines, bipy, organic azides, diazene derivatives, ketones, and carbodiimides. Abstract : The first base‐free terminal uranium phosphinidene metallocene was prepared and it showed a distinctively different reactivity compared to the related thorium phosphinidenes.